Implementation of modified trapezoidal commutation scheme for speed control of 1 kW BLDC motor - Sholihah, Ratih Mar'atus; Fahrul, Fahrul; Kurniawan, Adhika; Mahmudi, Irwan (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2023)
The commutation process in brushless DC (BLDC) motors is done electrically and depends on the rotor position feedback. The Six-Step method is the most commonly used method in BLDC control, as it is easy to implement. However, this method has a high root mean square (RMS) current. On the other hand, a perfect sinusoidal commutation method is very complicated. Therefore, this research proposes a simple modified scheme of trapezoidal commutation circuits that can produce sinusoidal BLDC output voltage. This circuit can still responsively control the speed of the BLDC motor. This scheme uses 2 Arduinos. Pulse width modulation (PWM) signal from Arduino2 is then combined with hall signals from Arduino1, resulting in six outputs which are modified electrical commutation signals. This commutation signal is used as a MOSFET controller in a 3-phase inverter to produce a sinusoidal waveform. The average efficiency obtained when implementing the commutation is 75 % at low and high speeds.